Emotional Analysis for Malayalam Text to Speech Synthesis Systems - Deepa P. Gopinath , Sheeba P.S and Achuthsankar S. Nair (4th International Conference: Sciences of Electronic, Technologies of Information and Telecommunications March 25-29, 2007, 2007)
The inclusion of emotional aspects into speech can improve the naturalness of speech synthesis system. The different emotions - sadness, angry, happiness are manifested in speech as prosodic elements like time duration, pitch and intensity. The prosodic values corresponding to different emotions are analyzed at word as well as phonemic level, using speech analysis and manipulation tool PRAAT. This paper presents the emotional analysis of the prosodic features such as duration, pitch and intensity of Malayalam speech. The analysis shows that duration is generally least for anger and highest for sadness, where as intensity is highest for anger and least for sadness. A new prosodic feature called rise time/fall time which can capture both durational and intensity variation, is introduced. The pitch contour which is flat for neutral speech shows significant variation for different emotions. The detailed analysis considering the duration of different phonemes reveals that the duration variation is significantly more for vowels compared to consonants